PENAKSIR RASIO REGRESI LINEAR UNTUK RATA-RATA POPULASI MENGGUNAKAN VARIABEL TAMBAHAN, KOEFISIEN VARIASI DAN KOEFISIEN KURTOSIS - Malini Anggraeni; Sigit Sugiarto; Rustam Efendi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This paper discusses three ratio regression linear estimators for population mean Y using two auxiliary variables X and , Z using the coefficient of variation and coefficient of kurtosis on simple random sampling. This paper is a review of the article Singh et. al [Statistics in Transition 10(1): 85-100]. The three estimators are biased estimators and their mean square errors are determined. Each estimator compared to the value of the mean square error. Comparison shows that the estimator with the minimum mean square error is an efficient estimator.